The myth of tightening credit rating standards in the market for corporate debt - Krystyniak, Karolina; Staneva, Viktoriya (Journal of Banking & Finance, 2024)
This study revisits the existing evidence of a downward trend in credit rating standards indicating that CRAs have become more conservative over time. We find that the time-series variation in the proxy for rating standards is mostly driven by the market-based variables in the model, specifically market capitalization and idiosyncratic volatility. We examine an alternative specification of the model, incorporating risk characteristics of rated firms relative to those of the average firm in the economy, and find it to have a higher explanatory power. Most importantly, we find little evidence of increased conservatism over time, in contrast to prior studies.